Que font les solutions fondées sur la nature aux politiques de gestion des risques liés à l’eau ? - Joana Guerrin; Sara Fernandez; Ludovic Drapier; Anna Serra-Llobet; Catherine Roche (Développement Durable et Territoires)
The concept of "nature-based Solutions" (NbS) has been gaining traction since the 2010s in international arenas, but also in many national and sub-national territories. In the field of water-related risks (particularly droughts and floods), NbS seem to be in line with the ecological turn of these public policies. NbS are presented as adaptive projects, cheaper and more bottom-up than so-called grey infrastructures – such as dams, reservoirs or embankments. For their instigators, these solutions help preventing water-related risks, while also benefiting biodiversity. Beyond the official definition proposed by the IUCN, what are NbS in practice, on the ground? What are their effects on territories, populations and public policies? Do they represent a real change in terms of public policies to prevent water-related risks? This special issue features seven contributions that contribute answering these questions and offer a critical look at NbS and their implementation. The introduction to this special issue provides a state-of-the-art on NbS and water-related risks, presents the seven contributions, and suggests future avenues for research to continue investigating such concept.